A review of genera and described Afrotropical species of Tetracampinae (Hymenoptera: Tetracampidae), with description of a new genus from East Central Africa - Gumovsky, Alex (Zootaxa, 2016)
The genera and described Afrotropical species of Tetracampinae Förster (Hymenoptera: Chalcidoidea, Tetracampidae) are reviewed. Despite the vague nature of some generic concepts, eight genera are recognized for the subfamily, i.e. Cassidocida Crawford, Diplesiostigma Girault, Dipriocampe Bouček, Epiclerus Haliday, Foersterella Dalla Torre, Niticampe Bouček, Tetracampe Förster, and the newly described Kilomotoia Gumovsky gen. n. The latter genus is established for Kilomotoia kitoko Gumovsky sp. n., collected from abandoned cultivated areas in the humid forest zone of North East Democratic Republic of Congo (Ituri forest, Ituri Province, environs of Mongbwalu village) and Central Uganda (Mabira forest, environs of Najembe village). Kilomotoia is distinguished from other tetracampine genera by the possession of a flattened dorsum, large abrupt pronotum, relatively long and laterally depressed gaster having gastral tergites II–V with medially emarginate posterior margins, and the hypopygium extending to the apex of gaster as sharply pointed mucro. The four hitherto described Afrotropical tetracampine species are reviewed based on available museum material, with Cassidocida africana Ferrière transferred to Foersterella as F. africana (Ferrière) comb. n., E. agromyzae (Risbec) and E. plectroniae (Risbec) confirmed as species of Epiclerus (as transferred earlier from Foersterella by Bouček 1958 and Bouček & Askew 1968), and Cassidocida orthopterae Risbec transferred to Closterocerus (Eulophidae, Entedoninae) as C. orthopterae (Risbec) comb. n. New diagnostic characters are proposed for the subfamily and some genera, and a comparative character table provided for tetracampine genera.